HUBUNGAN ANTARA INTERAKSI ORANG TUA DAN ANAK DENGAN PERKEMBANGAN BAHASA DAN KOGNITIF ANAK USIA (4-6 TAHUN) DI TK-MUSLIMAT AL HIDAYAH KEPANJEN - Mevia, Indah Nadhyfa Zahara; Ilmiah, Widia Shofa; Indriati, Ina (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Children are the biggest investment for the nation and family because children are the nation's next generation. Parents' active role in children's development is very necessary. Parenting style is the total interaction between parents and children, where parents provide encouragement for children by changing behavior, knowledge and values that are considered important for parents so that children can be independent, grow and develop healthily and optimally, have self-confident, curious, friendly, success-oriented. The type of research used in this research is an observational or ex post facto study using a cross sectional approach. The population in this study was all students and parents of Kindergarten A and Kindergarten B classes at TK-Muslimat Al-Hidayah Kepanjen in November 2023, totaling 147 people. The sample technique uses purposive sampling. The number of samples in this study was 60 people who were divided into two groups of equal size. The research results showed that the majority of respondents, 36 (60%) of them, had good parent-child interactions. Most of the respondents, 36 (60%) people, had good language development. Most of the respondents, 36 (60%) people, had good cognitive development. There is a relationship between parent-child interaction and language development in children aged (4-6 years) with Pvalue = (0.000) < (0.05). And the relationship between parent-child interaction and the cognitive development of children aged (4-6 years) with Pvalue = (0.000) < (0.05).